Aktualisasi Prinsip Continuous Improvement dalam Kepemimpinan Responsif Kepala PAUD Islam Terpadu al-Ikhlas Bumiayu Brebes - Wiyani, Novan Ardy (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2019)
This descriptive qualitative research is intended to obtain a description of the actualization of the continuous improvement principle in responsive leadership, the head of the Islamic Integrated Islamic Education Institute of Al-Ikhlas, Bumiayu District, Brebes Regency. The data in this study were collected using interview, observation, and documentation techniques. The author uses the data source triangulation technique to obtain valid research data. Valid research data are then analyzed using inductive data analysis techniques. The results showed that the actualization of the principle of continuous improvement in responsive leadership of the head of the Islamic PAUD Integrated al-Ikhlas in the Bumiayu sub-district of Brebes district was carried out by implementing six steps. First, diagnose problems in the implementation of integrated PAUD programs. Second, formulate solutions to problems in the implementation of integrated PAUD programs. Third, develop an improvement plan to overcome problems in the implementation of integrated PAUD programs. Fourth, condition resources to overcome problems in the implementation of integrated PAUD programs. Fifth, implement an improvement plan to overcome problems in the implementation of integrated PAUD programs. Sixth, evaluate the results of improvements to overcome problems in the implementation of integrated PAUD programs.